Elementary Art School of Folk Dance and Music in the Context of Regional Culture-Oriented Schools in Slovakia - Krušinská, Martina (Central European Journal of Educational Research, 2021)
In the study, we present the basic goals, content, strategies and organisational forms of education of the Elementary Art School of Folk Dance and Music in Ružomberok. The basic information about the school is supplemented with the ideas of its founder and the school principal, as well as the photo documentation of this school environment. We analyse this school model in the broader context of elementary regional culture-oriented schools, which began to develop in Slovakia after 1989. In connection with the school reform in 2008, the educational content of such schools was transformed and defined in the State Education Programme in the subject of Regional Education and cross-cutting topic Regional Education and Folk Culture. In addition to other alternative and innovative educational programmes in Slovakia, the regional culture-oriented school represents a domestic model of education, which is based on the historical and cultural peculiarities of individual regions of Slovakia. Despite the uniform name, each school with this orientation can have a unique character expressed in its school curriculum.